Pelatihan Al-Barzanji Dalam Rangka Menumbuhkan Kecintaan Kepada Nabi Muhammad Saw Se-Kecamatan Tuah Madani Kota Pekanbaru Provinsi Riau - Ningsih, Wirda; Supri, Supri; Muhammad Fauzi, Irfan; Hariati, Haryuni; Ikhsan, Eri; Bahri, Zainul; Iqral, Muhammad (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2023)
This community service aims to foster Rasulloah's love for the community, especially those who are Muslim in the Tuah Madani district of Pekanbaru, Riau. The training program for Al-Barzanji was designed and implemented using the PAR (Participatory Action Research) method, which involves researchers and participants in collaboration to encourage active participation, feedback, and joint knowledge creation. One proof of the transformational power of this training is the fact that people recognize how the training has changed their understanding of the personality of the Prophet Muhammad. One of the main results of the training session was that the participants were able to convey their knowledge and were able to recite the Barzanji salawat